2021
DOI: 10.2147/jpr.s310368
|View full text |Cite
|
Sign up to set email alerts
|

Moderate to Severe Osteoarthritis Pain and Its Impact on Patients in the United States: A National Survey

Abstract: Purpose Osteoarthritis (OA) is one of the most common causes of chronic pain and a leading cause of disability in the US. The objective of this study was to examine the clinical and economic burden of OA by pain severity. Patients and Methods We used nationally representative survey data. Adults ≥18 years with self-reported physician-diagnosed OA and experiencing OA pain were included in the study. OA pain severity was measured using the Short Form McGill Pain Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
(95 reference statements)
1
15
0
Order By: Relevance
“…Over time, a cursory overview of PUBMED, the As identified though in an article designed to examine correlations between pain severity and levels of anxiety and depression in adults with osteoarthritis patients, Fonseca-Rodrigues et al [8] using four databases from inception up to 14 January 2020 including 12 original articles and 121 studies, with a total of 38 085 participants, mean age 64.3 years old showed a moderate positive correlation between pain severity and depressive symptoms that cannot be readily overlooked. In addition, Schepman et al [9] who employed a nationally representative survey to generate data concluded that cases reporting moderate to severe pain on a daily basis often exhibited signs of depression, while Furlough et al [10] found a correlation between osteoarthritis disease duration and depression symptoms in cases with either hip or knee osteoarthritis. Barowsky et al [11] show that osteoarthritis and major depression appear to share common genetic risk mechanisms, one of which centers on the neural response to the sensation of mechanical stimulus that should be explored further.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, a cursory overview of PUBMED, the As identified though in an article designed to examine correlations between pain severity and levels of anxiety and depression in adults with osteoarthritis patients, Fonseca-Rodrigues et al [8] using four databases from inception up to 14 January 2020 including 12 original articles and 121 studies, with a total of 38 085 participants, mean age 64.3 years old showed a moderate positive correlation between pain severity and depressive symptoms that cannot be readily overlooked. In addition, Schepman et al [9] who employed a nationally representative survey to generate data concluded that cases reporting moderate to severe pain on a daily basis often exhibited signs of depression, while Furlough et al [10] found a correlation between osteoarthritis disease duration and depression symptoms in cases with either hip or knee osteoarthritis. Barowsky et al [11] show that osteoarthritis and major depression appear to share common genetic risk mechanisms, one of which centers on the neural response to the sensation of mechanical stimulus that should be explored further.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is a key contributor to pain, poorer health status and life quality, productivity and activity impairments. In addition, the presence of depression, often linked to pain, and more evident in the face of severe pain [19,20] may increase the risk for restless sleep among cases with osteoarthritis of the knee [21], and according to Furlough et al [10] many reports state that osteoarthritis, the most common joint disease, often produces lengthy periods of chronically intractable joint stiffness and swelling, as well as multiple functional, social, occupational, and emotional challenges and restrictions, as well as feelings of depression that flow from this [19,20]. Depressive presence may also impact surgical outcomes negatively [6], as well as sleep disturbances, overweight or obesity, pain, plus the presence of comorbid health conditions [22], hence surgeons and others have been increasingly encouraged not to neglect to screen for any undue depressive manifestations in their osteoarthritis clients [23], especially in light of the possible associations between a subject's psychological profile and their somatosensory function and brain structure [30].…”
Section: Resultsmentioning
confidence: 99%
“…In Japan, OA is a leading cause of years lived with disability, with the average age of patients around 70 years [ 1 ], similar to patients with OA in the US [ 2 ] and EUR [ 21 ]. In our study, the patients in Japan were, on average, older than those in the US and EUR, predominantly female, with milder severity of OA and greater reluctance and fear, possibly driven by concerns around safety risks associated with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…OA is strongly age-related and the most common cause of disability in the elderly, limiting their ability to carry out daily tasks and activities, and impacting their overall quality of life [1,2]. Effective treatment options are limited, and international guidelines for the management of OA recommend initial pharmacologic and non-pharmacologic approaches, followed by appropriate surgical intervention for those who do not achieve adequate pain relief and functional improvement [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, prevalence rates for osteoarthritis in our three highest classes ranged from 10.8% to 16.9% which is lower than the 23.7% reported for individuals the United States. 58 However, both of these painful conditions are associated with sleep disturbances 59,60 that may lead to reports of higher levels of morning fatigue. While causes of non-cancer pain are not routinely assessed in oncology patients, our findings suggest that these common comorbidities need to be evaluated and managed by oncology clinicians or primary care providers.…”
Section: Differences In Clinical Characteristicsmentioning
confidence: 99%